Isolation and identification of metabolites from ethyl acetate leaf extract of Solenostemma argel - Hassabelrasoul, Hanaa; Moriguchi, Maiko; Kang, Bubwoong; Siribel, Awatif Ahmed; Kuse, Masaki (Agriculture and Natural Resources, 2021)
Solenostemma argel is well-known in some parts of Sudan as a medicinal plant, where it is used as an anti-spasmodic, antidiabetic and anti-inflammatory because of its many useful secondary metabolites. This study identified and quantified the major metabolites of ethyl acetate extracts of S. argel leaves. Dried leaves of S. argel were macerated, extracted and subjected to liquid-liquid partitioning. The metabolites of the ethyl acetate extract were purified and isolated using a combination of chromatographic techniques (silica gel column chromatography and preparative thin layer chromatography). The structures of the isolated compounds were identified using infrared and nuclear magnetic resonance spectroscopy. The results showed that the three major metabolites of the ethyl acetate extract of S. argel leaves were kaempferol with 0.1% yield, kaempferol-3-O-β-D-glucopyranoside (astragalin) with 6.0% yield and kaempferol-3-O-[α-L-rhamnopyranosyl (1→2)-β-D-glucopyranosyl with 16% yield.